Bioethics and reciprocity in the acknowledgement of rights and duties - Villarroel Soto, Raúl (Acta Bioethica, 2009)
From a hermeneutic perspective, this article analyzes the statute of medicine as a healing art, considering its particular technical characteristic and its differences with other technical knowledge that delivers goods. This difficulty is compounded by the eruption of technical implementations and moral changes of modernity, which threaten effective practice and places its essential identity at risk. Currently it is understood that Medicine is more than the mere application of techniques and specialized knowledge, and that all responsible medical interventions should adjust their definition to the complex and essentially multidimensional nature of human beings, which is not realized by mere technical explanations or techniques that attempt to envision its vastness and plurality.